Overeducation, skill mismatches, and labor market outcomes for college graduates - Peter J. Sloane (IZA World of Labor, 2014)
There is evidence that many college graduates are employed in jobs for which a degree is not required, and in which the skills they learned in college are not being fully used. Most of the literature on educational or skill mismatch is based on cross-sectional data, providing information at just one point in time. Drawing meaningful conclusions about mismatch, its dynamics, and its relationship to wages, job satisfaction, and job mobility requires panel data, which can reach more nuanced conclusions by allowing for individual differences, e.g. choosing a job because it offers compensation.
Keywords: I20; J24; 330; overeducation; skill mismatch; overskilling; graduates